Survival of elderly patients with multiple myeloma—Effect of upfront autologous stem cell transplantation. (July 2016) - Merz, Maximilian; Jansen, Lina; Castro, Felipe A.; Hillengass, Jens; Salwender, Hans; Weisel, Katja; Scheid, Christof; Luttmann, Sabine; Emrich, Katharina; Holleczek, Bernd; Katalinic, Alexander; Nennecke, Alice; et al.
Abstract: Background: The aim of this study was to determine the value of upfront autologous transplantation (ASCT) in elderly patients (60–79 years) with myeloma. Methods: We analysed relative survival (RS) of patients diagnosed in 1998–2011 and treated with ASCT within 12 months after diagnosis in Germany (n = 3591; German Registry of Stem Cell Transplantation) and compare RS with survival of myeloma patients diagnosed in the same years in Germany (n = 13, 903; population-based German Cancer Registries). Results: Utilisation of ASCT has increased rapidly between 2000–2002 and 2009–2011 (60–64years: 7.0–43.0%; 65–69 years: 6.6–23.7%; 70–79 years: 0.4–4.0%). Comparison of 5-year RS of patients from the general German myeloma population who have survived the first year after diagnosis with 5-year RS of patients treated with ASCT revealed higher survival for transplanted patients among all age groups (60–64: 59.2% versus 66.1%; 65–69: 57.4% versus 61.7%; 70–79: 51.0% versus 56.6%). RS increased strongly between 2003–2005 and 2009–2011 for the general German myeloma population (+8.5%) and for patients treated with ASCT (+11.8%). Differences in RS between these groups increased over time from +1.9% higher age-standardised survival in transplanted patients in 2003–2005 to 5.2% higher survival in 2009–2011. Conclusion: We conclude that upfront ASCT might be a major contributor to improved survival for elderly myeloma patients in Germany. Highlights: Utilisation of autologous transplantation (ASCT) in elderly patients has increased rapidly in the last decade. Survival increased strongly in the last decade for the general myeloma population. This effect was even more pronounced in elderly patients treated with ASCT. ASCT in elderly patients might be a contributor to the seen survival improvement.